PENGARUH PUPUK HAYATI ENDOMIKORIZA ASAL AKAR MERANTI (Shorea sp) TERHADAP BIBIT TANAMAN GANDARIA (Bouea marcophlla) DAN RAMBUTAN (Nephelium appaceum) - Swietenia Frela Manuputty; Johan M. Matinahoru; Hendrik Steven S.E. Aponno (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
This study aims to determine and analyze the effect of endomycorrhizal biofertilizer solution from meranti roots on the growth of gandaria (Bouea marcophylla) and rambutan (Nephelium appaceum) seedlings. This study was conducted in Honitetu village, Kairatu District, West Seram Regency to collect endomycorrhizal samples from meranti roots and continued with the implementation of research in Suli village, Salahutu District, Central Maluku Regency from January 2025 to May 2025. The method used in the study was a completely randomized design with 2 factors and 3 replications. The first factor was the type of fertilizer consisting of A0 (without fertilizer), A1 (endomycorrhizal biofertilizer) and A2 (NPK Fertilizer). While the second factor was the type of plant consisting of B1 (gandaria) and B2 (rambutan). The parameters observed were plant height (cm), number of leaves (blades), leaf length (cm), leaf width (cm) and percentage of root infection (%). The results showed that the interaction between fertilizer type treatment and plant type had a very significant effect on all growth parameters. However, the interaction of factors A and B only affects the leaf width parameter.